UTILIZING COMPUTER BASED TEST APPLICATIONS TO MEASURE EMPLOYEE ACHIEVEMENT AT CLASS II IMMIGRATION OFFICE SUKABUMI - Ayi Abdurahman; Mila Rosmaya; Rasona Sunara Akbar (Polteknik Imigrasi, 2023)
The use of exam applications in Kantor Imigrasi Kelas II Sukabumi still uses open sources software, therefore it doesn’t fit the needs. Existing exam applications are still limited in available features. This community service aims to support schools in adopting CBT (Computer Based Test) in administering exams. The problems identified include weaknesses in the existing software and limitations in immigration officer literacy regarding its use. The method of implementing this community service is Service Learning. Activities consist of surveys and CBT software development, training, and mentoring. The implementation of the initial study identified the weaknesses of the existing application, namely regarding aspects of effectiveness and the required features that were unavailable. CBT development is conducted by enhancing usability through adding features and convenience. Training and mentoring are carried out to improve mastery and effectiveness of CBT use. The evaluation showed an increase in the immigration officer understanding of the application, the ability to make evaluations, satisfaction and the effectiveness of using the application. Other outputs were also fulfilled: the CBT application (UHW-CBT Kantor Imigrasi Sukabumi version), training modules, user manuals, intellectual property rights, and publications. This program has increased the adoption of CBT, which can be seen from the aspects of CBT software availability, use, literacy, a form of evaluation and recap, and test score ranking. The follow-up plan for this program is ongoing assistance according to partner needs.